Inhibitory effect of metformin and pyridoxamine in the formation of early, intermediate and advanced glycation end-products. - Saheem Ahmad (Public Library of Science (PLoS), 2013)
Background Non-enzymatic glycation is the addition of free carbonyl group of reducing sugar to the free amino groups of proteins, resulting in the formation of a Schiff base and an Amadori product. Dihydroxyacetone (DHA) is one of the carbonyl species which reacts rapidly with the free amino groups of proteins to form advanced glycation end products (AGEs). The highly reactive dihydroxyacetone phosphate is a derivative of dihydroxyacetone (DHA), and a product of glycolysis, having potential glycating effects to form AGEs. The formation of AGEs results in the generation of free radicals which play an important role in the pathophysiology of aging and diabetic complications. While the formation of DHA-AGEs has been demonstrated previously, no extensive studies have been performed to assess the inhibition of AGE inhibitors at all the three stages of glycation (early, intermediate and late) using metformin (MF) and pyridoxamine (PM) as a novel inhibitor. Methodology/principal findings In this study we report glycation of human serum albumin (HSA) & its characterization by various spectroscopic techniques. Furthermore, inhibition of glycation products at all the stages of glycation was also studied. Spectroscopic analysis suggests structural perturbations in the HSA as a result of modification which might be due to generation of free radicals and formation of AGEs. Conclusion The inhibition in the formation of glycation reaction reveals that Pyridoxamine is a better antiglycating agent than Metformin at all stages of the glycation (early, intermediate and late stages).